Upcycling: práticas barroco-mestiças nas artes visuais: ressignificando materiais, memórias e procedimentos artísticos - Perez, Gislaine Nascimento da Silva (2024)
This is a multidisciplinary work that falls within the field of knowledge of the Visual Arts. Its theoretical and methodological scope includes the concepts of semiotics of culture, semiosphere, unpredictability, explosion and memory by LOTMAN; culture, baroque, miscegenation and memory by PINHEIRO; complexity and memory by MORIN. It uses the syntactic and comparative method to show the importance of multiple connections within each work. The objective of the research is to study and record the creative process of Upcycling acting together with artisanal procedures, in the transformation of one sign into another sign. The research problem stems from the fact that, although each area of knowledge of the visual arts has its own specificity, can we say that upcycling is a common and transversal theme among them, that is, it corresponds to important, urgent and present issues in our daily lives and in the environment? Are the activities and attitudes directed towards the many forms of preservation and sustainability of natural life and its materialities (plants, vegetation, fruits and objects of all kinds and variations) satisfied with official discourses and/or those of the media and social networks or, with another focus (increasing the field of demand and complexity), do they demand modes of composition, relationship and connection – similar to other creative languages – that, going beyond or even challenging the very commonplace of said discourses and bypassing the beaten dichotomy between preservation/degradation, ultimately dedicate themselves to incorporating nature into culture through multiple translations that are already far from the evolutionary, linear and progressive scope of capitalism? The hypothesis, which emerged from empirical research, is that there is an intercommunication between the areas of architecture, interior design and fashion, which involves important issues such as the preservation of natural resources, sustainability, quality of life, conscious, ethical and socially fair consumption, a recovery of artisanal work and local culture. There is also a practice on the social networks YouTube and Instagram of sharing and publicizing artisanal and artistic processes and procedures, which are rescued through affective memories, and which were expanded with the Covid19 pandemic, with the aim of mitigating the damage caused by isolation and social distancing. To answer these questions, the author directed the empirical study to the research modality according to the qualitative approach, of an applied, bibliographic and participatory nature: as a researcher, she participated in the creation process, conducted and interacted with the procedures and results. Therefore, it was concluded that the process of creative reuse, Upcycling, allows us to resignify materials and products that would otherwise be discarded, thrown in the trash, transforming them into unique pieces, of greater value and/or quality, without going through chemical recycling procedures, rescuing memories and putting into practice the artisanal, do-it-yourself, making the method of syntactic and comparative connection important, because it shows the importance of multiple connections in each work, which not all Upcycling can achieve, because sometimes the syntactic relationship found causes a greater or lesser interplay between the elements that are in play, an interplay not mentioned by the media and social networks. Through the syntactic and comparative method, we can observe a relationship that is more conducive to multiple meanings. The work is divided into three chapters: the first deals with Upcycling in its state of the art; the second addresses Baroque-Mestizo Practices in the Visual Arts: resignifying materials, memories and artistic procedures; the third deals with the Semiotics of Culture and the Open-Air Market, a space inhabited by signs of culture